Excess nutritional disorders in children aged 1 to 9 years. Educational intervention strategy - Hernández Medina, Guillermo; Vilaú Suárez, Wilman Meylin; González Contreras, Susana Isabel (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: Childhood overweight and obesity in the world, constitute one of the most important health problems; presenting itself as a chronic disease of multifactorial origin, which is characterized by excess fat in the organism. Objective: To design an educational intervention strategy on nutritional disorders due to excess in children from 1 to 9 years old belonging to the Pilot Basic Work Group, Policlínico 5 de septiembre, in the period 2022 to 2023 Method: A descriptive and cross-sectional research was carried out. The universe consisted of 831 children and the sample consisted of 139 children diagnosed as obese and overweight. Theoretical and empirical methods such as interview and questionnaire were used for data collection. Results: there was a predominance of female sex, age group 1 to 3 years, overweight, obesity as family history; skin infections behaved as the diseases most related to nutritional disorders due to excess; insufficient knowledge of parents about obesity, risks, causes and consequences for the health of their children was identified, they saw children without a danger or risk of complications from such early ages of life. Conclusions: family lifestyles have an impact on the nutritional status of children, being of vital importance to apply the educational intervention strategy to modify these factors in order to have a better health and quality of life in children.